Identification of Zygosaccharomyces yeasts isolated from honeybee environment - Petra Javůrková; Kateřina Vočadlová; Jaroslav Motis; Hana Žáková; Michael Rost; Vladislav Čurn; Karel Beneš (Journal of Central European Agriculture)
While the bee microbiome has been relatively well studied at the bacterial level, information about the bee fungal communities is still sparse and does not reflect their importance. From the bee larvae of honey bee (Apis mellifera), bee bread and a mix of corbicular pollen, twenty yeast isolates belonging to the genus Zygosaccharomyces were obtained. Based on the D1/D2 region sequencing, the yeast isolates were identified as Z. rouxii (larvae), Z. favi (bee bread) and Z. mellis (mix of corbicular pollen). For the specific PCR-based detection of the most abundant yeast Z. rouxii, two species-specific primer pairs targeting the ITS region were designed. Because yeasts and their metabolites can play an important role in bee development, further investigation was focused on the production of ergosterol, an ecdysone precursor. HPLC detection of ergosterols was used and it has been found that ergosterol levels are highly variable across the monitored species and isolates and do not correlate with biomass production. The highest production of ergosterol in the Z. rouxii isolate was 6.2 mg/g dry biomass, in Z. mellis 2.3 mg/g dry biomass.